2013
DOI: 10.1016/j.jnutbio.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin decreases renal triglyceride accumulation through AMPK–SREBP signaling pathway in streptozotocin-induced type 1 diabetic rats

Abstract: Diabetic kidney disease has been associated with the presence of lipid deposits. We assumed that curcumin, a polyphenol, would attenuate the tissue dyslipidemic condition through activation of 5' adenosine monophosphate (AMP)-activated protein kinase (AMPK) phosphorylation and suppression of sterol regulatory element-binding protein (SREBP)-1c in the kidney and would prevent renal progression in experimental type 1 diabetic rats. Diabetes was induced with streptozotocin (STZ) (55 mg/kg) by intraperitoneal inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 53 publications
(57 reference statements)
0
57
1
5
Order By: Relevance
“…Transcriptional activation of SREBP-1 can also be upregulated by insulin [44] , glucose [45] , and LXR [46] . High-glucose-induced SREBP-1 was mediated by AMPK in T1D rats [47] . Uttarwar et al [48] showed that in primary rat mesangial cells, high-glucose (30 m M ) treatment within 1 h could transcriptionally activate SREBP-1, which works through EGFR-PI3K-Akt signaling.…”
Section: Srebp-1 Serves As a Mediator For The Crosstalk Between Glucomentioning
confidence: 92%
“…Transcriptional activation of SREBP-1 can also be upregulated by insulin [44] , glucose [45] , and LXR [46] . High-glucose-induced SREBP-1 was mediated by AMPK in T1D rats [47] . Uttarwar et al [48] showed that in primary rat mesangial cells, high-glucose (30 m M ) treatment within 1 h could transcriptionally activate SREBP-1, which works through EGFR-PI3K-Akt signaling.…”
Section: Srebp-1 Serves As a Mediator For The Crosstalk Between Glucomentioning
confidence: 92%
“…It is the main curcuminoid found in the spice turmeric, a plant alkaloid obtained from ground rhizome of the perennial herb Curcuma longa (13). According to investigations, curcumin has multiple biofunctional activities including anti-inflammatory, antioxidant, anti-cancer, anti-diabetes and chemo preventative activities (14)(15)(16)(17)(18).…”
Section: Nakhostinmentioning
confidence: 99%
“…Several natural AMPK activators, including curcumin, monascin, ankaflavin, and berberine, yielded promising results in preclinical models of NASH and of CKD [35,37,39], and the potent synthetic AMPK-activating dithiolethione oltipraz is being evaluated in non-cirrhotic NAFLD patients in a Phase 2 RCT (clinicaltrials.gov ID: NCT01373554).…”
Section: Role Of Energy and Nutrient Sensors 5 0 -Amp-activated Protmentioning
confidence: 99%